HUBUNGAN STATUS GIZI DENGAN USIA MENARCHE PADA SISWI SMP NEGERI 1 KUNTO DARUSSALAM TAHUN 2016 - Refni Oktaviani; Nanda Novziransyah (Jurnal Riset Hesti Medan, 2018)
Menarche is the first period experienced (menstruation)  by every adolescent who will enter puberty. The age when a girl began menstruating are very varied. Several recent studies indicate that the age of menarche in adolescence has decreased in recent years. The decline in the age of menarhe caused by several factors, one of them  is nutritional status. This type of research is used observational analytic to determine the relationship of nutritional status and the age of menarche in junior high school 1 Kunto Darussalam 2016 with cross sectional approach. The population in this research were all students of Junior high school 1 Kunto Darussalam totaling 210 people. Consecutive sampling method is used to take a sample with a sample of 68 people overall. The collected data include consist of primary data and secondary data. Primary data was collected by direct measurement and questionnaires, secondary data obtained from the Administration School. Analysis techniques data used are analysis techniques data univariate and bivariate. Hypothesis testing was doing at the level of significance of 0.05 or 95%.The results of this research shown the average age of menarche in junior high school 1 Kunto Darussalam 2016 is 11.66 years. From the results showed that there are differences in the average age of menarche between the nutritional status Underweight, Normalweight, Pre-Obesity and Obesity. It was found that the average age of menarche earlier occurred in student years Obesity is 10.25. Based on the analysis using Chi-Square(p-value = 0.013), it can be concluded that there is relationship between nutritional status and age of menarche. From  results of this research suggested to the adolescent  to live a life style and a healthy life style, so that it can achieve normal reproductive health.Key words : menarche, nutritional status